Passing Interest : Racial Passing in US Novels, Memoirs, Television, and Film, 1990-2010 - Nerad, Julie, 1969- (Book collections on Project MUSE., 2014)
"The first volume to focus on the trope of racial passing in novels, memoirs, television, and films published or produced between 1990 and 2010, Passing Interest takes the scholarly conversation on passing into the twenty-first century. With contributors working in the fields of African American studies, American studies, cultural studies, film studies, literature, and media studies, this book offers a rich, interdisciplinary survey of critical approaches to a broad range of contemporary passing texts. Contributors frame recent passing texts with a wide array of cultural discourses, including immigration law, the Post-Soul Aesthetic, contemporary political satire, affirmative action, the paradoxes of "colorblindness," and the rhetoric of "post-racialism"--